The pro-tumorigenic roles of granzyme B: mechanisms and therapeutic implications - Zhang, Yubi; Huang, Han; Xie, Linjun; Li, Chunhong; Zhou, Xiangyu (Frontiers in Immunology, 2026)
Granzyme B (GZMB) is an effector molecule primarily expressed by cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells. Historically, GZMB expression levels have served as a marker of immune activity, indicative of the potency of anti-tumor immunity. However, recent evidence increasingly demonstrates that GZMB also exerts immunosuppressive effects within the tumor microenvironment. Beyond CTLs and NK cells, GZMB derived from multiple immune and tumor cells promotes tumor initiation and progression by regulating biological processes such as extracellular matrix remodeling, epithelial-mesenchymal transition, and angiogenesis. This paper summarizes the pro-tumor sources and mechanisms of GZMB, providing a comprehensive understanding of its clinical significance to guide more holistic GZMB-based anti-tumor therapies.